Traitor in the shipyard : a Caroline mystery - Ernst, Kathleen, 1959-; Giovine, Sergio (Middleton, WI : American Girl Pub., 2013)
Caroline worries that British spies may be lurking in Sackets Harbor, but when strange things start happening at Abbott's Shipyard Caroline wonders if a spy, either someone she has known all her life or Papa's long-lost friend, is responsible.
Keywords: Mystery and detective stories; Spies -- Fiction; Friendship -- Fiction; Family life -- New York (State) -- Fiction; New York (State) -- History -- 19th century -- Fiction